Rational design of structure‐based vaccines targeting misfolded alpha‐synuclein conformers of Parkinson's disease and related disorders - Jose Miguel Flores‐Fernandez; Verena Pesch; Aishwarya Sriraman; Enrique Chimal‐Juarez; Sara Amidian; Xiongyao Wang; Caleb Duckering; Andrew Fang; Sara Reithofer; Liang Ma; Leonardo M. Cortez; Valerie L. Sim; et al. (Wiley, 2024)
Abstract Synucleinopathies, including Parkinson's disease (PD), multiple system atrophy (MSA), and dementia with Lewy bodies (DLB), are neurodegenerative disorders caused by the accumulation of misfolded alpha‐synuclein protein. Developing effective vaccines against synucleinopathies is challenging due to the difficulty of stimulating an immune‐specific response against alpha‐synuclein without causing harmful autoimmune reactions, selectively targeting only pathological forms of alpha‐synuclein. Previous attempts using linear peptides and epitopes without control of the antigen structure failed in clinical trials. The immune system was unable to distinguish between native alpha‐synuclein and its amyloid form. The prion domain of the fungal HET‐s protein was selected as a scaffold to introduce select epitopes from the surface of alpha‐synuclein fibrils. Four vaccine candidates were generated by introducing specific amino acid substitutions onto the surface of the scaffold protein. The approach successfully mimicked the stacking of the parallel in‐register beta‐sheet structure seen in alpha‐synuclein fibrils. All vaccine candidates induced substantial levels of IgG antibodies that recognized pathological alpha‐synuclein fibrils derived from a synucleinopathy mouse model. Furthermore, the antisera recognized pathological alpha‐synuclein aggregates in brain lysates from patients who died from DLB, MSA, or PD, but did not recognize linear alpha‐synuclein peptides. Our approach, based on the rational design of vaccines using the structure of alpha‐synuclein amyloid fibrils and strict control over the exposed antigen structure used for immunization, as well as the ability to mimic aggregated alpha‐synuclein, provides a promising avenue toward developing effective vaccines against alpha‐synuclein fibrils.